PG8 A 'COVID 19 – free cancer hub' cardiac arrest simulation. (10th November 2020) - Shah, Ashoke; Rowson, Mark; Harrison, Liam; Bidwai, Anita
Abstract : Introduction: The COVID-19 pandemic has undoubtedly had an enormous effect on surgical provision. Targeted re-opening of vital services, such as cancer operations, 1 have been implemented. St. Helen's hospital, a previous surgical day case unit has been designated as a COVID-free cancer hub as part of the Cheshire and Merseyside Alliance. With the new provision, patients with significant co- morbidities needing cancer surgery are considered for surgery. We conducted an in situ simulation to observe how these new teams worked together in dealing with an emergency situation. Method: An in-situ simulation was performed on the surgical ward using sim-man. We initially simulated chest pain, progressing to cardiac arrest. We conducted a pre and post simulation survey focussing on confidence and knowledge of cardiac arrest management. We also asked, with consent, certain participants for qualitative feedback after the scenario. Participants were multi disciplinary. Results: All participants found the scenario useful and 90% of participants felt that their confidence had improved. All participants knew how to escalate the situation appropriately. Only 20% knew where drugs and equipment were kept, this was further highlighted as a potential issue by the ward sister who was distracted and unable to be involved in patient management. Take home messages included, having a gate keeper, the addition of Personal Protective Equipment (PPE), and further simulation. Qualitative feedback themes included allocation of roles, speaking up and vigilance for wearing PPE. Discussion: The scenario highlighted important areas for consideration when managing a cardiac arrest during the COVID pandemic. The significant barrier witnessed was implementing PPE. Initially, the anaesthetist attempted to start chest compressions, before being reminded to don PPE, according to the new cardiac arrest algorithm for aerosol generating procedures. This created further delays to starting chest compressions as the correct PPE had to be located. The defibrillator operator repeatedly asked if they could proceed to give three stacked shocks while the team were donning, however the team were focussed on donning PPE. PPE presents difficulties, such as difficulty in communication and creating a distracting environment. Recommendations: We will now keep a bag stocked with PPE with the resuscitation trolley. Implementation of the HALT tool to break down communication barriers and of a gate keeper to limit the number of people entering the area. A folder containing COVID cardiac arrest algorithm, PCI and transfer protocols and allocation of roles at the start of each shift. References: NHS England and NHS Improvement, 2020. Clinical Guide For The Management Of Essential Cancer Surgery For Adults During The Coronavirus Pandemic . [online] NHS England; Royal College of Surgeons; British Association of Surgical Oncology. Available at: <https://www.england.nhs.uk/coronavirus/publication/clinical-guide-for-the-management-of-essential-cancer-surgery-for-adults-during-the-coronavirus-pandemic/> [Accessed 15 May 2020].